Scedosporium prolificans Fungemia. (1999) - Elsayed, Sameer; Lannigan, Robert; Chin-Yee, Ian
Abstract : Fungemia due to Scedosporium prolificans is described in a young woman with a relapse of acute lymphoblastic leukemia. Several days after starting reinduction chemotherapy, the patient presented with fever, neutropenia and blood cultures showing fungi on Gram stain. The patient died despite therapy with antifungal agents, including fluconazole and amphotericin B. Fungi grew from blood cultures, and was subsequently identified as Scedosporium prolificans .